How much does investment drive economic growth in China? - Duo Qin; Marie Anne Cagas; Pilipinas Quising; Xinhua He (Queen Mary University of London, Department of Economics, 2005)
Investment-driven growth has long been regarded as a key development strategy in China. This paper investigates empirically the validity of this view. Post-1990 data analyses and macroeconometric model simulations show that market demand has become a regular force in driving investment since reforms, that non-demand-driven investment growth contributes to increasing capital-output ratio far more than output growth, that government investment exerts a pivotal role in amplifying investment cycles, albeit effective in promoting employment, and that delayed and rising consumption from current investment surge can help sustain the impact of growth even with constant-returns-to-scale in the long-run GDP.
Keywords: E22; E62; R34; O23; P41; 330; Investment; Growth; Impulse response function; Cointegration; Granger non-causality; Investition; Wirtschaftswachstum; Kointegration; China; Makro\~AƒÂkonomischer Einfluss